The Number of Nephrons in the Kidney: A Relevant Question Implicated with Arterial Hypertension (International Journal of Medical and Surgical Sciences, 2014)
Stereological methods are used to obtain quantitative information about the three-di- mensional structures based on observations on cutting planes or, to a limited degree, projections. Stereological methods, which are used in biological research, and especially in the study of normal and pathological kidney, are powerful tools for the study of the kidney. The study of kidney development, with emphasis on subtypes of clusters found in this period of intrauterine life, has relevance to assess renal maturity and the consequences of changes in the normal process. Several studies have shown that the total number of nephrons varies widely in normal human kidneys. An association between the small number of nephrons and subsequent development of hypertension in adulthood has increasingly been accepted. There is sufficient experimental and clinical evidence to conclude that blood pressure is associated with the number of nephrons, although this concept is not unanimous in the literature.
Keywords: Stereological methods; Quantitative information; Kidney; Number of nephrons; Hypertension